Cambridge IELTS 3 with answers editon : examination papers from University of Cambridge ESOL Examinations - Cambridge University Press (Cambridge : Cambridge University Press, 2003)
Insight into IELTS offers comprehensive preparation for the IELTS examination, developing skills, language and familiarity with the test format for each paper progressively.
Keywords: International English Language Testing System; English language -- Textbooks for foreign speakers -- Study guides; Universities and colleges -- Entrance examinations